PENGARUH MODEL PROBLEM BASED LEARNING DENGAN BANTUAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XI MIPA SMAN 4 PADANG - Fania Melinda (Jurnal Edukasi dan Penelitian Matematika, 2021)
Matematics Learning result in a SMAN 4 Padang still in the low category because in the learning process teacher don’t activated students finding math draft. The solution is use of the problem based learning with the help learning videos. The study was intended to see there is an effect learning participants who studied with an advanced PBL learning model and a learning video with learners who learned with conventional learning. This kind of research is a quasy experiment and static group design research. The research population is class XI MIPA student in SMAN 4 Padang that register on learn year 2021/2022. Data collection in the study is done using the final test data of the learning tests analysed using the t-test.  Based on the final test  result analysis with minitab software, assistance gained P-value = 0.00 on a real level = 0.05, which states that the learning mathematics student learning with the  Learning problem model  with the help of a learning videos is better than the learning participants with direct learning or conventional learning  in class XI MIPA SMA Negeri 4 Padang.      Keywords– The Problem Based Learning, Conventional, Learning Videos ,Mathematics Learning Result